1998
DOI: 10.1002/jlb.64.3.368
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-stimulated TNF-α release from cultured rat Kupffer cells: sequence of intracellular signaling pathways

Abstract: We recently hypothesized that lipopolysaccharide (LPS) stimulation of rat Kupffer cells to induce tumor necrosis factor alpha (TNF-alpha) release requires internalization of LPS, acidification of endosomes, elevation of intracellular calcium, protein kinase C (PKC) activation, and protein tyrosine kinase (PTK) activation. This study uses inhibitors in pulse-chase experiments to determine the sequence of events of intracellular signals required for LPS-stimulated TNF-alpha release from Kupffer cells. Inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…5,6) The doses and effects of the inhibitors on the target signaling cascades were well examined in previous studies. 6,7) TiO 2 -concentration dependency of TNF-α release (particle size: 40 nm) was already examined in the Western blot analysis using anti-TNF-α antibody in Fig. 2, Inset in the present study, and also in other references.…”
Section: Methodssupporting
confidence: 56%
See 1 more Smart Citation
“…5,6) The doses and effects of the inhibitors on the target signaling cascades were well examined in previous studies. 6,7) TiO 2 -concentration dependency of TNF-α release (particle size: 40 nm) was already examined in the Western blot analysis using anti-TNF-α antibody in Fig. 2, Inset in the present study, and also in other references.…”
Section: Methodssupporting
confidence: 56%
“…The inhibitor concentrations were referred from earlier papers. 6,7,10) The administered dose and expected inhibitory effects of the biochemical reagents inside cells are listed in Table 1. Ten minutes after pretreatment with the reagents, 40-nm TiO 2 particles were added to the wells to be 50 µg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…12,13 Although cytochalasins have been used to block LPS uptake in several cell types, this molecule has also been shown to prevent downstream signaling as a consequence of LPS exposure. [32][33][34] Interestingly, Poussin et al 12 showed that cytochalasin D did not prevent LPS-dependent p38 MAPK and NF-B activation in THP-1 cells. In their study, cytochalasin D actually increased interleukin-8 secretion after LPS treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A time lapse of 15 to 30 min between LPS binding and LPS-induced responses such as cytokine release and adhesion was observed, which suggests that a time-consuming process such as internalization is necessary to enable signaling (93,315). Indeed, several, but not all, studies have revealed that blocking internalization or endosome fusion also blocks LPS-induced signaling (93,315,427,431). Although the precise mechanisms are not completely understood, it has been shown that monomeric LPS is transported into the cell to the Golgi complex, thus activating the cell.…”
Section: Cd14mentioning
confidence: 99%